Modelagem e análise de tensão em estrutura óssea com implante metálico, através do método dos elementos finitos - Hayasaki, Cláudio Luís [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The goal of this paper was to simulate through the Finite Element Method, the bone structure of rabbits (tibia), when subjected to a determined static transversal loading, and validate the numerical model obtained in the software Ansys. The mechanical behaviour of biomechanical structures, as tibia, femur, bones in general, are too much similar as mechanical structures, for example beams, bars, pipes, bridges, trusses, and so on. There were several difficulties in generating the three-dimensional model; we can numerate them. The first was to build the model exactly with all the irregular surfaces. For solve this problem, we measured along the length of the tibia for each five millimeters, beginning on the position of the implant. The second difficulty was to separate different materials that constitute the body of the bone, for instance, the cortical bone and the medular bone, as well as the region of implant of titanium. We differentiate the regions where each type of bone occurs, including the osseointegrated region. The third difficulty was to represent the load that acted over the bone structure. We adopt the load as a distributed pressure located over the region of the implant. The finite element model was simulated by Ansys software, where was applied tetrahedricals elements. For validating the model, the results were checked with the bibliography revision. We compare the results of intensity of maximal stress generated by the model with the maximal stress obtained experimentally. We conclude that was a reasonable approach, considering the accuracy of the constructed model.
Keywords: Método dos elementos finitos; Prótese; Biomecânica; Osseointegração